Imitation, Myth and Violence, Today and in the Past - Grande, Per Bjørnar (European Scientific Journal, ESJ, 2016)
In this article on imitation and violence I wish to interpret violent relations between human beings as founded on imitation of each other desires. (A desire for what other people desire.) Imitation, the desire to have what other people desire, is both the root to success and the root to violence. The article is inspired by the French philosopher, René Girard’s (1923-2015) theory on imitative desire. In my view, societies are continually threatened by violent imitation, and, at the same time, imitation is the factor which creates dynamic societies and cultures. Human beings are driven by desiring what other people desire, by wanting what others want. The challenge is to be able to create a society where one can freely follow one’s imitative desires and, at the same time, prevent violence. Desire today is, because violence is less accepted, manifest in a less physically violent way than before. Nonetheless, desire today creates scapegoats in a more psychological manner.